Scrutiny on Indonesian EFL Teachers’ Willingness to Understand and Implement the TPACK in VLE - Surayya, Siti Ayu; Asrobi, Maman; Farizi, Zukhruf (Universitas Pendidikan Ganesha, 2021)
During this pandemic, all countries focused on the issue of transforming the education system, media, teaching strategies, and materials, from face-to-face teaching and learning to teach in a Virtual Environment (TVE)-based, including in Indonesia. However, this sudden change of situation made all education systems change in a hurry. The fact that English teachers are more proficient at applying their content and pedagogical knowledge than technological knowledge makes this study aim to determine how willing teachers are to add and apply their TPACK, particularly in TVE at the moment, and also to reveal the effect of willingness to increase TPACK with a willingness to apply TPACK. The respondents in this survey were 43 EFL teachers. The instrument used in collecting data is a questionnaire. Descriptive statistics, normality and homogeneity tests, and independent t-tests were used in the quantitative data analysis. The data shows that most Indonesian EFL teachers are at the median level of readiness to learn and practice TPACK. However, there is no relationship between willingness to understand and willingness to apply TPACK among English teachers. This finding influences the perspective of educators and researchers on how external pressures need to be reduced and teachers in Indonesia to need internal motivation towards technology-based education.